RETRACTED ARTICLE: IMPDH2 is highly expressed in breast cancer and predicts unfavorable prognosis. (2nd January 2021) - Zhao, Yueming; Yang, Yawen; Dai, Jixing; Xing, Dejun; Dong, Ying
Abstract: We, the Editor and Publisher of Biomarkers, have retracted the following article: Yueming Zhao, Yawen Yang, Jixing Dai, Dejun Xing & Ying Dong (2018) IMPDH2 is highly expressed in breast cancer and predicts unfavourable prognosis, Biomarkers, DOI: 10.1080/1354750X.2018.1496360 The authors have requested retraction of their article after being unable to reach a consensus regarding authorship. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".